Conversation Analysis on the use of Non Competitive Overlap - Egipto, Genesis (International Journal of Arts, Sciences and Education, 2022)
Conversation analysis focuses on interactive and practical construction of everyday interchanges in which people interact on a moment-by-moment, turn-by-turn basis. This study aimed to examine the non-competitive overlap used, and the gender issues and concerns among the university students in their ordinary conversation. The three-part process discourse analytic technique: (Record-Transcribe-Analyze (R-T-A) method was used. Audio-recording was employed as an instrument in gathering the data. Data were analyzed using frequency distribution and results show that terminal overlap is the most commonly used non-competitive overlap, while the least is continuers. Further, in the findings on gender issue and concerns, it was found that female-to-female conversation has the highest frequency and percentage in their issues and concerns. Thus, it is concluded that non-competitive overlap is being used in ordinary conversations to maintain the conversation’s flow, encourage someone who is talking, and let the speaker know that the receiver is listening.